Synthesis and characterization of Zn and Co monocarboxy-phthalocyanines and investigation of their photocatalytic efficiency as TiO2 composites - Sevim, Altug Mert (Elsevier BV, 2017)
Abstract In this study, synthesis of a group of novel A 3 B-type non-symmetrically tetrasubstituted zinc(II) and cobalt(II) phthalocyanines bearing one carboxy group (4-mercaptobenzoic acid/4-hydroxybenzoic acid) and three 4- tert -butylphenoxy substituents was achieved by a statistical condensation reaction of the corresponding two phthalonitriles. These four new phthalocyanines have been characterized by using elemental analyses, UV–vis, FT-IR, 1 H NMR and mass spectroscopic techniques. MPcs were incorporated into TiO 2 semiconductors to prepare TiO 2 -MPc composites as heterogeneous catalysts. The novel composites were characterized by X-ray diffraction (XRD), infrared (FTIR) and diffuse reflectance analysis. The characterization results show that MPcs are anchored on the surface of TiO 2 through CO O TiO 2 bonds and anatase structure of TiO 2 remains unchanged after the sensitization process. The optimum loading of the dyes on TiO 2 ( ca . 8.4 μmol/g TiO 2 ) was almost independent of the amount of TiO 2 used. The new TiO 2 -MPc composites were used to test their photocatalytic activity on decomposition of 4-chlorophenol under visible light. In contrast to untreated TiO 2 , all photocatalysts prepared in this study were highly effective on 4-chlorophenol under visible light and almost total photodegradation was accomplished.